Academic Contributions to the UNESCO 2019 Forum on Education for Sustainable Development and Global Citizenship - Vuong, Quan-Hoang; Vinh, Le Anh; Trung, Tran (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This volume comprises a series of research articles dedicated to the UNESCO 2019 Forum on Education for Sustainable Education and Global Citizenship. Given the imperative of education in sustainable development, especially in developing countries, the volume covers a wide range of topics: the mobility and mental health of international students, reading habits and academic achievements of junior high school students, core competencies of mid-level managers in higher education, adoption of an international publishing standard, legal rights for education and socio-cultural adaptation of ethnic minorities, and, most recently, students' learning behaviors during the COVID-19 pandemic.